2018
DOI: 10.1177/0038040718757720
|View full text |Cite
|
Sign up to set email alerts
|

Latino/a Student Threat and School Disciplinary Policies and Practices

Abstract: Using a nationally representative sample of approximately 3,500 public schools, this study builds on and extends our knowledge of how ‘‘minority threat’’ manifests within schools. We test whether various disciplinary policies and practices are mobilized in accordance with Latino/a student composition, presumably the result of a group response to perceptions that white racial dominance is jeopardized. We gauge how schools’ Latino/a student populations are associated with the availability and use of several spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…When expanded, results showed that teachers were more likely to label African American males as "troublemakers" and indicate a pattern of misbehavior and that these indications were linked to more severe discipline and suggestions for suspensions. The relationship found in this study is supported by higher incidences of Black students being referred to the office for behavioral infractions despite similar behavior to that of other students (Anyon et al, 2014;Huang, 2018); this relationship extends to Hispanic students as compared to White students as well (Welch & Payne, 2018). To add to the challenge, once students get to the office they typically receive more severe and more exclusionary discipline than their White peers (Anyon et al, 2014, Huang, 2018, Welch & Payne, 2018.…”
Section: Discipline Effectssupporting
confidence: 57%
“…When expanded, results showed that teachers were more likely to label African American males as "troublemakers" and indicate a pattern of misbehavior and that these indications were linked to more severe discipline and suggestions for suspensions. The relationship found in this study is supported by higher incidences of Black students being referred to the office for behavioral infractions despite similar behavior to that of other students (Anyon et al, 2014;Huang, 2018); this relationship extends to Hispanic students as compared to White students as well (Welch & Payne, 2018). To add to the challenge, once students get to the office they typically receive more severe and more exclusionary discipline than their White peers (Anyon et al, 2014, Huang, 2018, Welch & Payne, 2018.…”
Section: Discipline Effectssupporting
confidence: 57%
“…For example, using a nationally representative sample of children in 8 th graders, Wright et al () found that prior teacher reports of aggressive behavior explained Black‐White and Hispanic‐White disparities in school suspension. However, a growing body of research suggests that disparities persist even when scholars consider differences in individual behavior problems (Ramey, ; Rocque, ; Skiba et al, ) and variation in school incidents of violence and misbehavior (Irwin et al, ; Payne and Welch 2012; Welch & Payne, , ). Moreover, if behavior were the primary factor behind child social control, it would follow that we would observe similar disparities in both criminalized and medicalized child social control, as schools would ostensibly rely on all possible social control strategies.…”
Section: The Social Structure Of Child Social Controlmentioning
confidence: 99%
“…When these patterns are considered in the context of criminalization and medicalization as repressive or restitutive social controls, disparities in school social control reflect systemic racial and economic inequality in the United States. Specifically, a large body of research suggests that support for the implementation and utilization of harsh or punitive social control policies and practices increases as the size of the minority and marginalized population increase relative to the White or middle‐class population (Payne and Welch 2012, Payne & Welch, ; Welch & Payne, , ). While less is known about the implementation of restitutive controls, recent research suggests that schools with larger White student bodies are more likely to implement restorative disciplinary practices (Payne & Welch, ; Payne & Welch, ; Welch & Payne, ), and schools with relatively larger White student bodies have higher enrollments of students on behavioral IEPs and Section 504 behavior plans (Ramey, ).…”
Section: The Social Structure Of Child Social Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…"magna cum laude"). In the worst-case-scenario, they lead to a student's expulsion, the longterm consequences of which have been described as a "school-to-prison pipeline" (Kim, Losen, and Hewitt 2010;Mittleman 2018;Welch and Payne 2018). This definitional power extends far beyond the realm of education, into the world of literature (Franssen and Kuipers 2013), fashion (Mears 2010), business (Khurana 2002), and as we will see below, sports.…”
Section: Talent Is Whatever Is So Definedmentioning
confidence: 99%